MÅLTIDER SOM FAMILIE-SKABELSE OG FRISÆTTELSE - Iversen, Trine; Holm, Lotte (Tidsskriftet Antropologi, 1998)
Trine Iversen & Lotte Holm: Meals and the Making of Family - and Individualisation In this article we discuss the role of meals in family life. In the sociological literature on food and eating the issue of meals is integrated in discussions of family life, social communities and socialisation of children and adolescents. In this empirically based article we focus on a group of Danish adults’ considerations about meals. On this basis we wish somewhat to modify the assumption which is implicit in the literature, as well as in public debate; namely, that the daily family meal is the foundation for integration of the individual household members into a group, i.e. that it is the basis for the making of the family. Our material shows that the family meal is indeed an ideal that adults strive to realise. However, adults 251 are ambigious in this endeavour, as they are very considerate about adolescents’ social activities outside the home. In faet we find that adults contribute to the process of individualisation which occurs during the teenage period, by accomodating mealtimes or accepting non-attendance at meals. The project of making the family appears to be an adult project, to which the adolescents are not expected to contribute. Rather, adults acknowledge the need and desire of adolescents to liberale themselves from the household unit.